Multifarious plant growth promoting ability of Pseudomonas extremorientalis RPB22 enhances chickpea (Cicer arietinum) growth - BAGUL, SAMADHAN YUVRAJ; PATEL, RITU RAJ; VISHWAKARMA, RITU; CHAKDAR, HILLOL; K, PANDIYAN; M, KUMAR; VELLAICHAMY, MAGESHWARAN; B L, RAGHUNANDAN; SRIVASTAVA, ALOKK KUMAR (The Indian Journal of Agricultural Sciences, 2026)
The present study was carried out during 2020–2021 at ICAR-National Bureau of Agriculturally Important Microorganisms, Mau, Uttar Pradesh to assess the plant growth-promoting potential of a bacterial isolate obtained from the hot water spring at Tattapani, Chhattisgarh. The hot spring exhibited a temperature of 80°C and a pH of 7.5. Molecular characterization identified the isolate as Pseudomonas extremorientalis strain RPB22. This strain showed tolerance to salinity up to 3% NaCl and temperature of 50°C. Strain RPB22 efficiently solubilized inorganic tri-calcium phosphate (333 ± 9 µg/mL) and potassium (10.5 mg/L). High-Performance Liquid Chromatography (HPLC) analysis revealed the production of several organic acids, predominantly malic acid, followed by oxalic acid. Seed treatment of chickpea with strain RPB22 led to a 2.75-fold and 2.17-fold increase in fresh root and shoot dry weight, respectively, while root volume increased 1.8-fold compared to the untreated control. These findings highlight the potential of P. extremorientalis RPB22 as a thermo-tolerant, multifaceted plant growth-promoting bacterium suitable for biofertilizer development in arid and semi-arid environments exposed to high temperatures.